OPTIMIZATION OF PROCESS PARAMETERS FOR MACHINING DIFFERENT MATERIALS ON CNC MACHINE-REVIEW - Mr. Vikram D. Patil; Mrs. Sonal Sali.; Mr. Dhiraj D. Shinde (International Journal of Innovations in Engineering Research and Technology, 2021)
Now a day the most important process is turning for manufacturing industry. It helps to increase production rate with high quality. In CNC turning operation the surface roughness (SR), material removal rate (MRR), power consumption, nose radius and etc. are the output parameters. To evaluate process parameters surface roughness and material removal ate is too much important. There are some process parameters for turning purpose which are more important and considered as input parameters to measure SR and MRR. The input parameters are cutting speed, feed and depth of cut. In this paper we will study different review papers with different input and output parameters so as to conclude which input parameter is most beneficial for their particular output parameter.